Chromium dynamics in soil - Abdol Rahim, Kartini (2016)
Due to increasing awareness of potential Cr toxicity, there is a pressing need to establish sensitive and robust Cr fractionation and speciation methodologies that will be enable separation of the two redox Cr species (CrIII and CrVI) from different environmental phases and their quantification. The intention of this work was to assess the behaviour of Cr species, especially CrVI, in soils and the factors controlling Cr solubility, fractionation, redox transformation rates and uptake by plants. The analysis methods relied on alkaline extraction in TMAH, liquid chromatography (LC) to separate the chromium species and inductively couple plasma mass spectrometry (ICP-MS) for quantification of chromium. The interference of 40Ar12C+ background peak at mass 52 was reduced by using the CCT-KED facility of the ICP-MS. A solution of 50 mM TRIS buffer, 40 mM NH4NO3, 10-5 M ammonium-EDTA at pH 7.0 was used as the chromatographic eluent. The method developed is suitable for determining CrVI in soil, following alkaline extraction in TMAH, but not for CrIII due to poor recovery, redox transformation and strong binding of CrIII with humic acid despite attempts to preserve the trivalent species using EDTA and heating. The extraction method was applied to assessing Cr speciation and fractionation in a wide range of soil ecosystems collected from urban sites in Wolverhampton, Nottingham, London and a historical sewage sludge disposal farm in Nottinghamshire. To predict soil CrVI content the use of TMAH-extractable Cr (CrTMAH) was better (R=0.911) compared to total soil Cr content (Crtotal; R=0.554). The same analytical approaches were also applied to the development of a method to determine isotopically exchangeable CrVI in soils. This employed isotopically enriched 50CrVI as a ‘spike’ isotope added to soils suspended in varying concentrations of TMAH in an attempt to resolve a consistent fraction of isotopically exchangeable, or ‘labile’, CrVIO42- in soil. It was apparent that, because of the slow exchange kinetics of CrVI in soils, it was difficult to determine a consistent isotopically exchangeable fraction. Nevertheless, the investigation did suggest a refinement of the simple TMAH extraction protocol could enable direct determination of labile soil CrVI. The kinetics of CrVI interaction with a geocolloid (humic acid) was assessed and humic acid was found capable of both reducing CrVI and binding with the resulting CrIII species. Finally, Cr uptake by maize grown on a historical sewage sludge disposal farm was assessed with several approaches to finding a correlation between Cr in soil and Cr uptake by plants. The concentration of CrVI in soil, and its solubility, could be reasonably well predicted from Crtotal or CrTMAH and soil properties. However, restricted uptake of CrVI by the maize plants, and probably reduction of CrVI to CrIII in the root system, made it impossible to predict Cr transfer to shoots or the speciation of the Cr in maize shoots. Overall, due mainly to the apparent ability of the maize plants to control uptake and speciation of CrVI, the produce was considered safe to be consumed by ruminants as regards CrVI content.